A KDEL Retrieval System for ER-Golgi Transport of Japanese Encephalitis Viral Particles - Wang, Robert YL (Viruses, 2016)
Evidence has emerged that RNA viruses utilize the host secretory pathway for processing and trafficking mature viral particles and for exiting the infected cells. Upon completing the complex assembly process, the viral particles take advantage of the cellular secretory trafficking machinery for their intracellular trafficking toward the Golgi organelle and budding or export of virions. In this study, we showed that Japanese encephalitis virus (JEV)-induced extracellular GRP78 contains no KDEL motif using an anti-KDEL-specific antibody. Overexpression of the KDEL-truncated GRP78 in the GPR78 knocked down cells significantly reduced JEV infectivity, suggesting that the KDEL motif is required for GRP78 function in the release of JE viral particles. In addition, we demonstrated the KDELR protein, an ER-Golgi retrieval system component, is associated with viral envelope proteins and is engaged in the subcellular localization of viral particles in Golgi. More importantly, accumulation of intracellular virions was observed in the KDELR knocked down cells, indicating that the KDELR protein mediated the intracellular trafficking of JE viral particles. Altogether, we demonstrated that intracellular trafficking of JE assembled viral particles was mediated by the host ER-Golgi retrieval system prior to exit by the secretory pathway.